Messages Revealed Through Figurative Language Used in “Lamb to the Slaughter” by Roald Dahl - Wilma Prafitri; Muhammad Alim Akbar Nasir (The Study Program of English Education of Palangka Raya University, 2023)
Semantics is the study of meaning in language. One of the linguistic features that can be considered in semantics is figurative language. Short stories are oases of figurative language and literary devices that are used in such a way that they portray a far deeper meaning then the words themselves do. Because the story uses figurative language, readers occasionally have trouble understanding its significance and message. In this study, the researchers examine Roald Dahl's short tale